Assessment of Weibull Parameter by Five Numerical Methods and Estimation of Wind Speed at Rotterdam, Netherland - Umair Abbas; G.S. Akram Ali Shah (Journal of Basic & Applied Sciences, 2016)
In this paper Weibull parameters(c and k) have been estimated on wind speed data of Rotterdam, Netherland. We have applied five numerical methods i.e. Modified Maximum Likelihood Method, Maximum Likelihood Method, Energy Pattern Method, Empirical Method and Method of Moments, to calculate the values of c and k. The parameters k and c have used to estimate the probability distribution function and average wind speed. The wind speed data on hourly basis from 2005-2014 have obtained from “Royal Netherlands Meteorological Institute”.